Smith & Tanagho's general urology - McAninch, Jack W.; Tanagho, Emil A., 1929-; Lue, Tom F. (McGraw-Hill Medical, 2013)
Offers a complete overview of the diagnosis and treatment of the diseases and disorders managed by urologic surgeons. This book delivers a clear, concise presentation of the etiology, pathogenesis, clinical findings, differential diagnosis, and medical and surgical treatment of all major urologic conditions.